Tindak Tutur Komisif dan Konstruksi Citra Politik dalam Spanduk Kampanye Berbahasa Sunda di Kota Bandung Tahun 2024 - Ammirulhaz, Moch Dhymas; Sudaryat, Yayat; Widyastuti, Temmy (Jurnal Bahasa dan Sastra, 2025)
This study aims to describe the form and meaning of commissive speech acts in Sundanese political campaign banners during the 2024 general and regional elections in Bandung. A qualitative descriptive approach was used, employing data in the form of banner and billboard texts collected through documentation during the campaign period. The data were analyzed using Searle and Sudaryat's speech act framework, focusing on the types of commissives (promises, offers, commitments, and support) as well as direct–indirect and literal–nonliteral forms. The results show that the dominant commissive speech acts are direct literal forms used to convey political promises explicitly and in a way that is easily understood by voters. These findings confirm the role of banners as a strategic political communication medium in building the image of candidates and influencing voter perceptions, while also enriching the study of political pragmatics in the Sundanese cultural context. Unlike previous studies that generally highlight directive or expressive speech acts in campaign media, this study confirms the dominance of direct literal commissive strategies in Sundanese-language banners and shows that the choice of explicit speech acts plays an important role in building the candidate's image of honesty and cultural closeness in the eyes of voters.